Analyzing changes of volatile components in dried pork slice by gas chromatography-ion mobility spectroscopy. Issue 1 (1st January 2020) - Chen, Mingjie; Chen, Tong; Qi, Xingpu; Lu, Daoli; Chen, Bin
ABSTRACT: The volatile organic compounds (VOCs) in different processing stages of dried pork slices (DPS) were analyzed by gas chromatography-ion mobility spectrometry (GC-IMS), which was used to construct the GC-IMS odor fingerprint spectrometry. The VOCs of raw meat, mixed meat, cured meat, semi-finished meat and finished meat were detected and analyzed by GC-IMS. The result shows that the main VOC species in DPS include alcohols and aldehydes, acids, ketones, heterocyclic compounds, aromatic hydrocarbons and esters. Except that the VOCs of mixed meat and cured meat were very similar, the odor component characteristics of DPS in other processing stages were significantly different. GC-IMS technology can effectively distinguish the volatile component differences of preserved meat samples at different processing stages. It is of profound significance to regulate and ensure the consistency of the VOCs in the processing of DPS.